Routledge handbook of modern Japanese history - Saaler, Sven; Szpilman, Christopher W. A. (Routledge, 2018)
"The Routledge Handbook of Modern Japanese History is a concise overview of modern Japanese history from the middle of the nineteenth century until the end of the twentieth century. Written by a group of international historians, each an authority in his/her field, the book covers modern Japanese history in an accessible yet comprehensive manner. The subjects featured in the book range from the development of the political system and matters of international relations, to social and economic history and gender issues, to post-war discussions about modern Japan's historical trajectory and its wartime past. Divided into thematic parts, the sections include: - Nation, empire and border - Ideologies and the political system - Economy and society - Historical legacies and memory. Each chapter outlines important historiographical debates and controversies, summarizes the latest developments in the field, and identifies research topics that have not yet received sufficient scholarly attention. As such, the book will be useful to students and scholars of Japanese history, Asian history and Asian Studies."--Provided by publishers
Includes bibliographical references and index
Keywords: Japan -- History -- 1868-; Japan -- History -- 1868- -- Historiography; Japan -- History -- Historiography -- 1868-; Aufsatzsammlung; Geschichte 1868-; Japan